Cerebral Blood Flow Changes in Multiple Sclerosis and Neuromyelitis Optica and Their Correlations With Clinical Disability - Zhang, Xue; Guo, Xi; Zhang, Ningnannan; Cai, Huanhuan; Sun, Jie; Wang, Qiuhui; Qi, Yuan; Zhang, Linjie; Yang, Li; Shi, Fu-Dong; Yu, Chunshui (Frontiers in Neurology, 2018)
Distinguishing relapsing-remitting multiple sclerosis (RRMS) and neuromyelitis optica (NMO) is clinically important because they differ in prognosis and treatment. This study aimed to identify perfusion abnormalities in RRMS and NMO and their correlations with grey matter volume (GMV) atrophy and clinical parameters. Structural and arterial spin labeling MRI scans were performed in 39 RRMS patients, 62 NMO patients and 73 healthy controls. The grey matter cerebral blood flow (CBF) values were voxel-wisely compared among the three groups with and without GMV correction. The regional CBF changes were correlated with the Expanded Disability Status Scale (EDSS) scores in the corresponding patient groups. Although multiple brain regions showed CBF differences among the three groups without GMV correction, only three of these regions remained significant after GMV correction. Specifically, both the RRMS and NMO groups showed reduced CBF in the occipital cortex and increased CBF in the right putamen compared to the control group. The RRMS group had increased CBF only in the medial prefrontal cortex compared to the other two groups. The occipital CBF was negatively correlated with clinical disability in the NMO group; however, the CBF in the right putamen was positively correlated with clinical disability in both patient groups. These findings suggest that there are perfusion alterations independent of GMV atrophy in RRMS and NMO patients. The regional CBF in the occipital cortex and putamen could be used as imaging features to objectively assess clinical disability in these patients.